PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN EDUCAPLAY UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS IV DALAM PEMBELAJARAN IPAS - Nurizzati, Dinda; Apriana, Dina; Subandi; Rostika, Reni; Thoibah, Zurriatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student activeness is a fundamental prerequisite in elementary science learning, yet classroom realities reveal that many students remain passive and insufficiently engaged in the learning process. This study aimed to enhance the learning activeness of fourth-grade students at SDN 2 Sandubaya through the implementation of the Problem Based Learning model assisted by Educaplay. This classroom action research employed the Kemmis and McTaggart model conducted over three cycles, each consisting of planning, action implementation, observation, and reflection. The research subjects were 26 students from class IV B at SDN 2 Sandubaya in science learning focusing on human needs and their fulfillment tools. Data were collected through direct observation using student activeness observation sheets and learning implementation sheets, then analyzed using descriptive quantitative techniques. The findings revealed a gradual improvement in student activeness from the initial condition of 28% (low category), increasing to 42% in cycle I (moderate category), 64% in cycle II (high category), and reaching 88% in cycle III (very high category). This improvement exceeded the established success indicator of 80%. The success of this research demonstrates that the integration between the problem-solving structure of Problem Based Learning and the interactive appeal of Educaplay effectively promotes optimal student engagement. In conclusion, the implementation of the Problem Based Learning model assisted by Educaplay effectively enhances student learning activeness in elementary science instruction.